Aryl Hydrocarbon Receptor Gene Polymorphism and its Association Towards Lung Cancer Risk and Clinical Outcomes - Budhwar, Sneha (My University, 2016)
The present study was focused to assess the vulnerability of an individual towards Lung cancer having a polymorphism in the exon10 (rs2066853) and two polymorphism in the intronic region (rs10250822, rs2282885) and rs7811989 of AhR. A case control study was performed on the North Indian population. Odds ratio and class interval were used to assess the potency of the association. p value were also calculated to find out the statistical significance of the analysis. Multivariate and univariate analysis were also performed to assess the survival rate. Cumulative cigarette smoking was interrogated to be a lead player along with other parameter responsible for the susceptibility towards lung cancer. The combinatorial effect of genotype and histological forms with combined effect of polymorphism was also studied and significant associations were found to exist. The present study provided us with wider platform to study the rs10250822, rs2066853, rs10250822, rs7811989 polymorphism. Statistically significant values were seen amongst the genetic variants of AhR and were found to have a great risk towards Lung cancer. Tobacco smoking was affirmed as congener along with other environmental contaminants and showed higher OR and therefore a strong association with lung cancer risk. Cumulative effect of polymorphism amongst the AhR variants was also shown to be highly associated with the risk towards Lung cancer. AhR rs10250822, rs2282885, rs7811989 were found to be maximally associated with the risk of Lung cancer.
Keywords: Lung Cancer; Polymorphism